2018
DOI: 10.1101/442376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Designing metabolic division of labor in microbial communities

Abstract: Microbes face a tradeoff between being metabolically independent and relying on neighboring organisms for the supply of some essential metabolites. This balance of conflicting strategies affects microbial community structure and dynamics, with important implications for microbiome research and synthetic ecology. A "gedanken experiment" to investigate this tradeoff would involve monitoring the rise of mutual dependence as the number of metabolic reactions allowed in an organism is increasingly constrained. The … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 90 publications
(123 reference statements)
0
31
0
Order By: Relevance
“…At this stage, we can only speculate what such cooperative benefits might be, but one can imagine that cells might not only differ in methionine uptake, but also in a number of other metabolic traits 21 . If so, this could allow for some form of metabolic division of labor, where subpopulations exchange metabolites in the same way as synthetic bacterial communities can exchange amino acids 8,[68][69][70][71][72] . Exploring these and other potential benefits of the long-term phenotypic heterogeneity in methionine uptake is an exciting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, we can only speculate what such cooperative benefits might be, but one can imagine that cells might not only differ in methionine uptake, but also in a number of other metabolic traits 21 . If so, this could allow for some form of metabolic division of labor, where subpopulations exchange metabolites in the same way as synthetic bacterial communities can exchange amino acids 8,[68][69][70][71][72] . Exploring these and other potential benefits of the long-term phenotypic heterogeneity in methionine uptake is an exciting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Other molecular assays, particularly mass spectrometry (MS)-based proteomics, can be applied to strain-type either isolates or communities [110]. This is also true for MS-or NMRbased metabolomics or metabolic flux measurements [111]. Of course, microbial culture physiology and direct imaging has been used to differentiate among strains since the earliest microbiology, and in some cases, these timetested methods can be applied to communities as well.…”
Section: Strategies and Approaches To Identifying Community Strain DImentioning
confidence: 99%
“…We showed that, in this controller architecture, there is a trade-off between robustness to environmental disturbances and robustness to perturbations in available resources to the genetic circuit. Placing different genetic circuit components in multiple cells has been proposed as a possible solution to relieve some resource sharing effects for larger genetic circuits [15], [21], [32]. However, our analysis shows that when fluctuations in cellular resources are considered, it is not possible to tune the population controller to be both robust to extracellular disturbances and to intracellular disturbances.…”
Section: Discussionmentioning
confidence: 88%